Earthworm powder as an alternative protein source in diets for common carp (Cyprinus carpio L.). (24th March 2015) - Ngoc, Tuan Nguyen; Pucher, Johannes; Becker, Klaus; Focken, Ulfert
Abstract: The increasing need for aquafeed resources and the finite availability of conventional feed resources are making it necessary to search for alternative high‐protein resources that are not used as human food. The earthworm Perionyx excavatus was tested as a feed ingredient in diets for common carp. An experiment was conducted to evaluate the potential of earthworm powder as a replacement for fishmeal. In a recirculation aquarium system, triplicate groups of five common carp ( Cyprinus carpio L.) were fed a control feed (fishmeal based protein), or experimental diets in which 30% (EW30), 70% (EW70), or 100% (EW100) of fishmeal protein was replaced by earthworm protein. Fish growth, feed digestibility and feed utilization were monitored. Growth rate, protein efficiency and energy retention in fish were similar (EW30, EW100) or higher (EW70) for diets containing earthworm meal compared to the control diet. Protein digestibility in EW30, EW70 and EW100 was higher than in the control diet, but in (EW100), lipid conversion was lower. We conclude that earthworm is a suitable partial replacement for fishmeal in feeds for common carp.